(untitled) - Robert Davis Cook (New York, 1995)
The book presents a modest amount of theory, discusses the nature of FE solutions, offers modeling advise, suggests computational problems, and emphasizes the need for checking the computed results
Keywords: finite element method - data processing,structural analysis ( engineering ) - data processing